Perforated ileal duplication cyst presenting with right iliac fossa pain mimicking perforated appendicitis - Ab Rashid, Islah Munjih; Tajri, Hafizan (Malaysian Medical Associations, 2008)
Enteric duplication is an uncommon malformation of the gastrointestinal tract which is either asymptomatic or presents with vague symptoms mimicking other more common pathology. It is most commonly diagnosed when complications such as bleeding, intestinal obstruction or perforation occurs. This is a case report of a patient with this condition presenting with right iliac fossa pain and localised peritonitis mimicking acute appendicitis.